2004
DOI: 10.1103/physreva.69.042104
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical parameter estimation using realistic photodetection

Abstract: We investigate the effect of imperfections in realistic detectors upon the problem of quantum state and parameter estimation by continuous monitoring of an open quantum system. Specifically, we have reexamined the system of a two-level atom with an unknown Rabi frequency introduced by Gambetta and Wiseman [Phys. Rev. A 64, 042105 (2001)]. We consider only direct photodetection and use the realistic quantum trajectory theory reported by Warszawski, Wiseman, and Mabuchi [Phys. Rev. A 65, 023802 (2002)]. The most… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…More generally, we may wish to estimate one or more numbers that parameterize the state, Hamiltonian, or overall evolution of a system. Such parameters can be estimated by making a continuous measurement on an evolving system and processing the measurement results [332][333][334][335][336][337]. Such a procedure has applications to metrology, such as the detection of weak force by monitoring a harmonic oscillator [336], or estimating the Rabi frequency of a two-level atom [333].…”
Section: Quantum Parameter Estimationmentioning
confidence: 99%
“…More generally, we may wish to estimate one or more numbers that parameterize the state, Hamiltonian, or overall evolution of a system. Such parameters can be estimated by making a continuous measurement on an evolving system and processing the measurement results [332][333][334][335][336][337]. Such a procedure has applications to metrology, such as the detection of weak force by monitoring a harmonic oscillator [336], or estimating the Rabi frequency of a two-level atom [333].…”
Section: Quantum Parameter Estimationmentioning
confidence: 99%
“…It is possible to formulate extended Kalman filters for such scenarios, in which one or more parameters appearing in the Hamiltonian are treated as static or dynamic variables to be estimated from a continuous measurement signal. Some general investigations have appeared on the sensitivity and optimization of such procedures (including analytic studies in the Gaussian framework and numerical studies allowing more general likelihood functions) [130][131][132]. A thorough analysis has been performed of using this strategy for broadband magnetometry with atoms [10], and it has been shown that real-time feedback can be exploited for significant gains in robustness.…”
Section: Quantum System Identificationmentioning
confidence: 99%
“…Finally, we combine these theories to consider the following case: a quantum system is monitored continuously in time by a classical system but we only have access to the results of non-ideal measurements performed on the classical system. Note that such joint systems have recently been studied by Warszawski et al [21,22,23] and Oxtoby et al [24]. Warszawski et al considered continuous-in-time monitoring of a quantum optical system with realistic photodections while Oxtoby et al considered continuous-in-time monitoring of a quantum solid-state system with a quantum point contact.…”
Section: Introductionmentioning
confidence: 99%